Element of system protection (System protection technology)
The objective of this module is to provide an overview of the function of protection schemes, including general protection philosophy and its impact on the operation of the system. Topics include: why protection is necessary? - the philosophy and objectives of protection, zones of protection - local and backup, causes and consequences of faults; tolerable and intolerable fault conditions, factors affecting relay application; the need for coordination.